2011
DOI: 10.1007/978-3-642-23765-2_45
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Relationships between Physiological Measures and Evaluation Metrics for 3D Interaction Techniques

Abstract: Abstract. This project aims to present a methodology to study the relationships between physiological measures and evaluation metrics for 3D interaction techniques using methods for multivariate data analysis. Physiological responses, such as heart rate and skin conductance, offer objective data about the user stress during interaction. This could be useful, for instance, to evaluate qualitative aspects of interaction techniques without relying on solely subjective data. Moreover, these data could contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…For example, CS has been reported to increase cortisol levels in saliva (Kennedy et al 2010) or to cause tachycardia (Hu and Stern 1999;Imai et al 2006). Furthermore, it seems that CS often correlates with facial pallor, sweating, and respiration rate variations (Johnson 2005) as well as with heart rate variability (Rieder et al 2011). Unfortunately, individual differences in autonomic regulation and variations caused by the experience but not by a negative reaction to it (sickness) make it challenging to predict CS based on variables such as the heart rate or respiration rate (Kiryu and Iijima 2014).…”
Section: On Biosignal-based Alternatives To the Ssqmentioning
confidence: 99%
“…For example, CS has been reported to increase cortisol levels in saliva (Kennedy et al 2010) or to cause tachycardia (Hu and Stern 1999;Imai et al 2006). Furthermore, it seems that CS often correlates with facial pallor, sweating, and respiration rate variations (Johnson 2005) as well as with heart rate variability (Rieder et al 2011). Unfortunately, individual differences in autonomic regulation and variations caused by the experience but not by a negative reaction to it (sickness) make it challenging to predict CS based on variables such as the heart rate or respiration rate (Kiryu and Iijima 2014).…”
Section: On Biosignal-based Alternatives To the Ssqmentioning
confidence: 99%
“…Physiological measurements, unlike subjective measurements, can provide real-time and objective data [3]. Thereby, many studies have explored the link between physiological responses and stress.…”
Section: Physiological Measurementsmentioning
confidence: 99%
“…This stresses the importance shown by previous research on attempting to move to more objective measurement methods, such as postural sway (Chardonnet, Mirzaei, and Merienne 2017) or biosignals. Previous studies have reported for cybersickness to increase the levels of cortisol in saliva (Kennedy, Drexler, and Kennedy 2010), cause tachygastria, correlate with sweating and respiratory rate variations (Johnson 2005) heart rate variability (Gavgani, Hodgson, and Nalivaiko 2017;Malińska et al 2015;Nakagawa 2015;Rieder, Kristensen, and Pinho 2011) and galvanic skin response (GSR) (Gavgani et al 2017). Other studies state that the onset of cybersickness is induced by specific factors (or triggers), but the increase in cybersickness depends on individual differences in autonomic regulation, which makes it difficult to detect it (Kiryu and Iijima 2014).…”
Section: Introductionmentioning
confidence: 99%